2021
DOI: 10.2196/29213
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Impacts of COVID-19 on a Sample of Australian Adults: Cross-sectional Survey and Sentiment Analysis

Abstract: Background The COVID-19 pandemic has had enormous impacts on people’s lives, including disruptions to their normal ways of behaving, working, and interacting with others. Understanding and documenting these experiences is important to inform the ongoing response to COVID-19 and disaster preparedness efforts. Objective The aim of this study was to examine the psychosocial impacts of COVID-19 on a sample of Australian adults. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We administered eight items developed ad hoc to rate on a 5-point scale, from (1 = not at all) to (5 = a lot), how much the COVID-19 have impacted participants’ life domains (i.e., personal/relatives’ health, family relationships, personal/family finances, work activities, personal course of study). At the time of this writing no appropriate validated pre-existing tool was available, thus the research team specifically constructed the eight items of the questionnaire in accordance with the literature, which identified specific key life domains (see Ryan et al, 2021 ). After confirming that this scale was mono-dimensional, χ 2 (20) = 52.388, p = < .001; RMSEA = 0.080 , 95% CI [0.054, 0.107], p = 0.031; CFI = 0.915, and reliable (α = .772), we adopted it as control variable in our statistical models.…”
Section: Methodsmentioning
confidence: 99%
“…We administered eight items developed ad hoc to rate on a 5-point scale, from (1 = not at all) to (5 = a lot), how much the COVID-19 have impacted participants’ life domains (i.e., personal/relatives’ health, family relationships, personal/family finances, work activities, personal course of study). At the time of this writing no appropriate validated pre-existing tool was available, thus the research team specifically constructed the eight items of the questionnaire in accordance with the literature, which identified specific key life domains (see Ryan et al, 2021 ). After confirming that this scale was mono-dimensional, χ 2 (20) = 52.388, p = < .001; RMSEA = 0.080 , 95% CI [0.054, 0.107], p = 0.031; CFI = 0.915, and reliable (α = .772), we adopted it as control variable in our statistical models.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, individuals’ mental health has also deteriorated: More people have suffered from depression ( Burke et al, 2020 ), anxiety ( Burke et al, 2020 , Qiu et al, 2020 , Wang et al, 2020 ), and distress ( Taylor et al, 2020 , Wang et al, 2020 ) because of the fear of COVID-19 ( Taylor et al, 2020 ), social distancing, lack of interaction with others ( El Omrani et al, 2021 , Oosterhoff et al, 2020 ), and limited physical activity ( Reigal et al, 2021 ). Previous studies have also found that financial difficulties are negatively related to mental health during the COVID-19 pandemic ( Campbell-Scherer et al, 2021 , Halford et al, 2020 , Ryan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 91%